Tree Species Influence Nitrate and Nitrous Oxide Production in Forested Riparian Soils - Charlene N. Kelly; Elizabeth A. Matejczyk; Emma G. Fox-Fogle; Jason A. Hubbart; Timothy P. Driscoll (Nitrogen, 2023)
Abundance of soil microbial nitrogen (N) cycling genes responsible for nitrification, denitrification, and nitrous oxide reduction may vary with tree species and N inputs, and these variables may be used to predict or mediate nitrate (NO3−) and nitrous oxide (N2O) from soil. Nitrification and denitrification rates have also been linked to tree mycorrhizal associations, as soil beneath species associated with arbuscular mycorrhiza (AM) shows greater nitrification rates than species forming ectomycorrhizal (ECM) associations. In this study, we integrated N microbial functional gene abundance in the soil influenced by six tree species in two sub-catchments receiving either high or low N inputs. The soils beneath the two ECM-associated tree species and the four AM-associated tree species were analyzed for inorganic N content and potential N2O flux and microbial gene abundance (nirK and nosZ) was quantified using qPCR techniques. Other parameters measured include soil pH, moisture, and organic matter. We determined that tree species influence NO3− and N2O production in riparian soils, particularly under high N enrichment. The soil beneath black cherry had the lowest pH, NO3− concentration, potential N2O production, and OM, though this result did not occur in the low N catchment. The strongest predictors of soil NO3− and N2O across the study sites were N enrichment and pH, respectively. These results provide a framework for species selection in managed riparian zones to minimize NO3− and N2O production and improve riparian function.